Evaluation of the Implementation of P5 in Strengthening the Character of Students in Junior High Schools in Sukajaya District, Sabang City - Azizah, Azizah; Zahraini, Zahraini; Syarfuni, Syarfuni (FKIP - Universitas Riau, 2025)
Character education is an important element in shaping students' moral, social, and emotional competencies, particularly within the context of the Indonesian Independent Curriculum. One strategy to strengthen students' character is through the implementation of the Pancasila Student Profile Strengthening Project (P5). This study aims to describe and analyze the implementation process of P5 in strengthening students' character, the assessment standards used, and the follow-up plan developed to improve the quality of education in junior high schools in Sukajaya District, Sabang City. This study used a qualitative descriptive method involving interviews, observation, and documentation. Informants included the principal, curriculum team leader, subject teachers, and students. The results showed that the implementation of P5 in State Junior High School 2 Sabang focused on a sustainable lifestyle theme through ecobrick activities, while State Junior High School 2 Sabang adopted an entrepreneurship theme through a school bazaar event. All implementations followed the four main stages of P5: planning, implementation, evaluation, and follow-up. Assessment emphasized authentic evaluation based on student participation, creativity, and collaboration. It can be concluded that the implementation of P5 made a positive contribution to strengthening students' character and improving contextual learning, although continuous improvement and teacher guidance are still needed.